Elite and Popular Religion: The Book of Hours and Lay Piety in the Later Middle Ages - Duffy, Eamon (Studies in church history, 2006)
The very phrase ‘elite and popular religion’ is laden with potentially misleading polarities. In talking about elite religion or popular religion, are we contrasting notions of orthodoxy with heterodoxy or superstition, or the religion of the clergy with the religion of the laity, or the religion of the rich with the religion of the poor, or the religion of the polite and educated with the religion of the unwashed and unlettered, or the religion of the thinking individual over against the religion of the undifferentiated multitude, or the disciplined and liturgically-based official religion of the institutional Church with something more charismatic, less structured - or some permutation of any of the above?